Pneumonia in Children under five years old in KPK: Symptoms and presentation - Mujtaba Gul, Muhammad Shehzad, Kashif Ali Khan, Muhammad Abbas, Muhammad Fawad, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The lung parenchyma is affected by pneumonia, an acute infectious disease that can be brought on by fungus, bacteria, or viruses. By vaccination, a healthy diet, and the abolition of environmental variables, pneumonia can be avoided. All worldwide deaths of children under the age of five are due to it. Aim: To prevent pneumonia with easy steps, and can be treated with easy, affordable medications with adequate care, early detection, and prompt admission of sick children to hospitals. Methods: This case series study was carried at pediatric department of district kohat hospital from august 2022 to Feb 2023. Ethical acceptance certificate was obtained from the hospital. Informed written consent was taken from those parents who were willing to answer and were fully qualified the inclusive criteria. Total 139 patients were enrolled in the study. The results were analyzed through spss-ver 24 Results: In clinical sign and symptoms highest ratio was seen in lethargy 33(23.74%) and lowest ratio seen in cyanosis 4 (2.87%), in gender wise the male 82(59%) presentation was more than females 57(41%). Lowest ratio of vaccination was seen in 2(28%) dose 6 and highest in non-vaccination was 21(44%) in dose 1. Conclusion: The health planners should concentrate on the missed epi schedule. Efficacy, we must employ media like radio, television, and newspapers Keywords: Pneumonia, education, health, presentation, Kohat